A wideband dielectric resonator antenna with switchable diversity patterns. Issue 4 (22nd May 2020) - Abdalrazik, Ahmad; Abdel-Rahman, Adel B.; Allam, Ahmed; Abo-Zahhad, Mohammed
Abstract: In this paper, a reduced-size dielectric resonator antenna with switchable diversity patterns is proposed. Ring- and linear-shaped slots are etched in the ground plane of the antenna so as to generate two modes $TE_{δ 11}^x$ and $TE_{δ 12}^x$ at a center frequency of 19 GHz. Moreover, two groups of PIN diodes are integrated into these slots to short one group of slots, and let the other group generates the required mode. Thus, the antenna is able to generate two switchable patterns with an envelope correlation coefficient of 0.4. Furthermore, the antenna size is reduced to half of its original size by placing a copper sheet over certain plane of the antenna structure. The antenna achieves wide bandwidths of 17.6–20.9 GHz (17.1 $\percnt $ ) and 18.3–21.6 GHz (13.8 $\percnt $ ) in cases of exciting $TE_{δ 11}^x$ and $TE_{δ 12}^x$ modes, respectively. The antenna also attainsa high gain of 7.1 and 3.2 dB at the center frequency.